Pendekatan Inward Experience dan Outward Behaviour sebagai Tawaran Model untuk Kajian Agama - Syafaq, Hammis (ISLAMICA: Jurnal Studi Keislaman, 2014)
This paper deals with the importance of inward experience and outward behavior in religious studies. The reason underlying this paper is that what insiders perform cannot be felt by outsiders. Experiences felt by practicing insiders constitute the internal aspect of religion which cannot be communicated to others; therefore it cannot be transferred to outsiders. This characteristic is often misunderstood by many observers of religion, and this leads to the gap between insiders and observers, particularly when the latterâs faith is different from that of former. This constitutes the major problem in the study of religion nowadays despite the fact that there have been progresses made by scholars in regard to empathic approach in the study of religion. The purpose of this approach is to bridge the gap between insiders and outsiders, while offering an understanding that insidersâ experiences can be called inward experience, while external behavior grasped by outsiders is called outward behavior. By doing so, prejudices and lurking attitudes among different religious believers can be avoided.